Unemployment Compensation in Milwaukee: Evaluating and Improving Cost Management - Zeman, Elizabeth; Stepien, David; Fuentes, Jeannette; Fontaine, Joe (My University, 2008)
This report assesses whether and how the City of Milwaukee could improve its Unemployment Compensation cost control and management by analyzing the city?s costs and administrative practices and evaluating the findings against the costs and practices of six comparable cities. The authors recommend that Milwaukee strengthen working relationships between central administrators and operating departments, establish benchmarks for tracking and evaluating Unemployment Compensation outcomes, and improve data collection.
For PA 869: Public Affairs Workshop, Domestic Issues